PERSEPSI LABEL HALAL PADA PRODUK MAKANAN DALAM KEMASAN OLEH MAHASISWA STKIP BABUNNAJAH PANDEGLANG BANTEN - Teguh Ardianto; Andri Imam Subekhi; Fajrin Noviyanto (International Journal Mathla’ul Anwar of Halal Issues, 2021)
Indonesia is a nation with moslems as the largest populations. As a nation with vast ranging cultures, Indonesia does also have many kinds of culinary and beverages. In a moslem community Halal status is important as a guideline for moslems. Therefore, MUI gives halal label so that people is easier to identify halal products. There are two problems in this research to focus. The first is about the implementation of halal label by MUI in the packaged food and drink products. The second focus is on how is the perception of students in STKIP Babunnajah toward the halal labialization of packaged food and drink products. This research used descriptive qualitative research approach. The instrument used to collect the data was by questionnaires delivered through google form. There were 15 questions in the questionnaires investigating products’ halal status. There were 40 respondents of the research consisting of 10 students for each year level. The study showed that halal label issued by MUI for packaged food and drink products has gone through careful examination by MUI. Moreover, the students in STKIP Babunnajah has the perception that halal product labeling was in accordance to sharia law.